Analisis Pengaruh Penerapan Program Ayah Mengantar Anak (GAMAS) Berkaitan dengan Fenomena Fatherless terhadap Perkembangan Self-Confidence Siswa pada Pembelajaran Sejarah - Offy Resdiantari; Aman; Maulano Barontuko (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
The issue of low self-confidence among students in learning activities is a serious concern, as it has a significant impact on active participation, critical thinking skills, motivation, and the courage to express opinions in class. Various approaches have been implemented, but most remain focused on pedagogical approaches in schools without involving the role of parents, particularly fathers. Therefore, this study offers an analysis of the implementation of the “Fathers Accompanying Children to School” (GAMAS) program on the first day of school as an innovative approach to involving fathers in the educational process. The research method used in this article employs a qualitative research method of literature review. The data sources used in this study come from various literature, such as books, mass media or newspapers, and other articles relevant to the research topic. The results of this study indicate that there is a correlation between the “Fathers Accompanying Children to School” (GAMAS) program and the development of students' self-confidence in history learning. Fathers' physical and emotional involvement in school activities directly provides psychological support that strengthens children's self-confidence. Through healthy self-confidence, students will be encouraged to participate more actively and be motivated to engage in learning. The implications of these findings show the importance of collaboration between schools and parents, especially fathers, in creating a learning environment that supports the development of students' character and potential.